Subgeneric classification of the bee genus Rediviva Friese (Hymenoptera: Apiformes: Melittidae) - Kuhlmann, Michael; Jürgensen, Lea-Sophie; Michez, Denis (Zootaxa, 2020)
For the first time a subgeneric classification of the oil-collecting bee genus Rediviva is presented. Five subgenera comprising 33 species are recognized based on morphological characters. Three of them are described as new: Deriviva subgen. nov., Albiviva subgen. nov. and Gigaviva subgen. nov.. The genus Redivivoides rendered Rediviva paraphyletic and is downgraded to subgenus level. A key is provided to enable the identification of subgenera.